Peningkatan Kemampuan Pemecahan Masalah Soal Cerita Matematika Siswa melalui Think Pair Share Berbantuan KACERGAM - Riska Zeli Wijayanti; Zerra Puspita Angellina; Lovika Ardana Riswari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to improve the mathematical word problem-solving skills of third-grade students at SD 2 Panjunan through the implementation of the Think Pair Share (TPS) learning model assisted by the Picture Story Card (KACERGAM) media. The study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of the planning, implementation, observation, and reflection stages. The research subjects were 13 third-grade students of SD 2 Panjunan. Data were collected through observation, tests, and documentation, while data analysis was carried out using descriptive quantitative and qualitative methods based on Polya's problem-solving indicators. The findings indicated that the implementation of the Think Pair Share model assisted by KACERGAM media effectively improved students' mathematical word problem-solving skills. The percentage of classical learning mastery increased from 61.5% in Cycle I to 84.6% in Cycle II, while the class average score increased from 72 to 88. Improvements were also observed in all problem-solving indicators, including understanding the problem, devising a plan, carrying out the solution, and reviewing the answer. Furthermore, students' learning activities became more active through independent thinking, pair discussions, and sharing discussion results with the class. Therefore, the Think Pair Share learning model assisted by KACERGAM media is effective in improving elementary school students' mathematical word problem-solving skills.